2003
DOI: 10.1128/iai.71.4.1833-1842.2003
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Sequences in Block 2 ofPlasmodium falciparumMerozoite Surface Protein 1 Are Targets of Antibodies Associated with Protection from Malaria

Abstract: Human antibodies to the block 2 region of Plasmodium falciparum merozoite surface protein 1 (MSP1) are associated with a reduced prospective risk of clinical malaria. Block 2 is highly polymorphic, but all known alleles can be grouped into three major types. Two of these types (the K1-like and MAD20-like types) contain type-specific sequences (found in all alleles of a particular type) that flank polymorphic tripeptide repeats. These repeats contain both type-specific and subtype-specific sequences. To evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
71
1
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 37 publications
7
71
1
3
Order By: Relevance
“…Our observation that MSP-1 19 induces a mixed IgG1/IgG3 response which then polarizes, with increasing exposure to infection, to IgG1 is consistent with previous reports (11,15,18,34), as is our observation that MSP-2 and GPI preferentially induce IgG3 antibodies (6,29,39,46). Polarized IgG1 responses are also reported for Pf155/RESA (17), crude schizont lysate (33), RAP-1 (44), and MSP-6 (50), while IgG3 responses are seen for a polymorphic C-terminal region (block 2) of MSP-1 (11), MSP-3 (11, 31), MSP-4 (51), and MSP-7 (50).…”
Section: Discussionsupporting
confidence: 82%
“…Our observation that MSP-1 19 induces a mixed IgG1/IgG3 response which then polarizes, with increasing exposure to infection, to IgG1 is consistent with previous reports (11,15,18,34), as is our observation that MSP-2 and GPI preferentially induce IgG3 antibodies (6,29,39,46). Polarized IgG1 responses are also reported for Pf155/RESA (17), crude schizont lysate (33), RAP-1 (44), and MSP-6 (50), while IgG3 responses are seen for a polymorphic C-terminal region (block 2) of MSP-1 (11), MSP-3 (11, 31), MSP-4 (51), and MSP-7 (50).…”
Section: Discussionsupporting
confidence: 82%
“…Thus, early studies have demonstrated the presence of naturally acquired antibodies against the N terminus (7, 9) and C terminus (13,28,31) of PfMSP1. The presence of such naturally acquired antibodies against MSP1 was later correlated to clinical protection in some, though not all, studies (8,10,12,14,24,25,26). Although the role of other portions of this large molecule remains mostly unknown, these studies have validated the N and C termini of PfMSP1 as solid subunit vaccine candidates against P. falciparum.…”
mentioning
confidence: 85%
“…personally diagnosed these patients, and after obtaining ethical consent to not treat them with drugs, actively followed them up twice a week for 2 months to guarantee that they did not develop malaria symptoms. Moreover, we analyzed independently the N and C termini of PvMSP1, as antibodies against both regions of the MSP1 of P. falciparum have been associated with clinical protection and acquired immunity (8,10,12,14,24,25,26). Strikingly, in spite of being the most immunogenic portion of PvMSP1 in natural infections and being capable of boosting (34), there was no association of antibody responses against the C terminus of PvMSP1 in survey A with clinical protection or risk of P. vivax infection (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The sequence was subcloned from the pPCR-Script vector into pGEX-2T to be expressed as a glutathione S-transferase (GST) fusion protein in Escherichia coli BL21(DE3) cells. Expression and purification followed manufacturers' protocols, as described previously for other MSP1 block 2 recombinant proteins (5,32).…”
Section: Methodsmentioning
confidence: 99%
“…One of these, the K1-like type, is the most common in all African populations (7) and contains the most complex subtype sequence diversity due to variation in different tri-and hexapeptide repeat sequences (28). Although subtype-specific human antibodies to K1-like repeats have been described (4,5) and are associated with protection from clinical malaria (32), the adaptive significance of the extensive repeat sequence polymorphism is not clearly understood. The present study explores the statistical distribution of sequence length variation in different parts of the K1-like repeats and identifies the primary sequences that are recognized by murine monoclonal and human serum antibodies.…”
mentioning
confidence: 99%